2014
DOI: 10.1159/000363372
|View full text |Cite
|
Sign up to set email alerts
|

Spectacle Independence after Cataract Extraction in Post-Radial Keratotomy Patients Using Hybrid Monovision with ReSTOR® Multifocal and TECNIS® Monofocal Intraocular Lenses

Abstract: Background: We report 2 patients who have undergone radial keratotomy (RK) preceding ReSTOR® multifocal intraocular lens (IOL; Alcon, Fort Worth, Tex., USA) implantation in their nondominant eyes and TECNIS® monofocal IOL (Abbott Medical Optics, Abbott Park, Ill., USA) in their dominant eyes. Methods: Retrospective review of 2 patients who underwent hybrid monovision with ReSTOR® multifocal and TECHNIS® monofocal IOLs at the time of cataract surgery after a remote history of RK. Results: Implantation of the Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…To our knowledge, there have been few case reports and no reviews investigating the use of multifocal lenses in patients with a history of RK. Two reports describe favorable patient satisfaction in 3 patients (5 total eyes) using a refractive-type multifocal IOL (Oculentis LS313-MF30; Soleko FIL611PVT),6,7 while a third describes 2 eyes of 2 patients that received a ReSTOR diffractive multifocal optic in the nondominant eye 8. While the aforementioned reports suggested acceptable levels of patient satisfaction and spectacle independence, there remains insufficient objective evidence supporting the routine use of advanced-optics IOLs in this patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there have been few case reports and no reviews investigating the use of multifocal lenses in patients with a history of RK. Two reports describe favorable patient satisfaction in 3 patients (5 total eyes) using a refractive-type multifocal IOL (Oculentis LS313-MF30; Soleko FIL611PVT),6,7 while a third describes 2 eyes of 2 patients that received a ReSTOR diffractive multifocal optic in the nondominant eye 8. While the aforementioned reports suggested acceptable levels of patient satisfaction and spectacle independence, there remains insufficient objective evidence supporting the routine use of advanced-optics IOLs in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…However, post-refractive patients may carry higher expectations and be motivated to reduce spectacle dependence after cataract surgery. To date, only 5 patient cases have been described regarding use of multifocal lenses in patients with prior RK (3 patients with refractive multifocal optic, 2 patients with diffractive multifocal optic),6–8 and no summative objective or subjective data are available. The intent of the current study is to report visual performance and subjective satisfaction in patients with prior RK that have undergone cataract surgery with implantation of an extended depth of focus (EDOF) IOL.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to visual acuity correction in patients undergoing RK with hyperopic shift and presbyopia, a possible and well-tolerated solution is represented by the implantation of multifocal IOLs, as reported by Kim et al [ 3 ] and Gupta et al [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tahzib et al 9 reported implantation of an Artisan toric phakic IOL and an aphakic IOL (Ophtec BV) in 2 patients with a history of RK. Similarly, Gupta et al 10 reported 2 cases in which patients with a history of RK had implantation of a multifocal IOL in the nondominant eye and a monofocal IOL in the dominant eye. To our knowledge, this is the first report of a patient successfully treated with a pseudoaccommodating toric IOL following RK.…”
Section: Jcrs Online Case Reports 2014; 2:73-77 Q 2014 Ascrs and Escrsmentioning
confidence: 96%